Experience with a naphthylmedetomidine-ketamine-hyaluronidase combination in inducing immobilization in anthropoid apes - Hess, L; Votava, M; Schreiberová, J; Málek, J; Horácek, M (Journal of medical primatology, 2010)
BACKGROUND: The aim of the study was to compare the effect of naphthylmedetomidine to medetomidine on the behavior of orangutans and chimpanzees. METHODS: The immobilization was performed as part of a medical examination in five chimpanzees and three orangutans. Following pre-medication with midazolam (0.70-1.20 mg/kg p.o.), naphthylmedetomidine (50-70 microg/kg), or medetomidine (20-30 microg/kg) was given with ketamine (3 mg/kg) and hyaluronidase (150 M.U.) into musculus deltoideus. RESULTS: We observed the distinct anti-aggressive effect of naphthylmedetomidine. The immobilization with naphthylmedetomidine was shallower and the influence on cardiac frequency less substantial compared to medetomidine. The overall sedative effect of naphthylmedetomidine lasted for less time, and its effect was incompletely antagonized with atipamezole in comparison to medetomidine. CONCLUSIONS: Naphthylmedetomidine could replace medetomidine for inducing immobilization and sedation. A combination of naphthylmedetomidine-ketamine is suitable for relocating animals to other cages or for painless medical examinations.
Keywords: Hyaluronoglucosaminidase; Ketamine; Pongo; hyaluronoglukosaminidasa; ženské pohlaví; mužské pohlaví; Pan troglodytes; Immobilization; zvířata; Animals; medetomidin; imobilizace; ketamin; Medetomidine; Female; Male